DOZ047.109: Impact of positive expiratory pressure breathing on gastroesophageal reflux: preliminary report in children with esophageal atresia and tracheoesophageal fistula and residual tracheomalacia. (24th June 2019) - Porcaro, F; Tambucci, R; Petreschi, F; Leone, P; Malamisura, M; Caldaro, T; De Angelis, P; Cutrera, R
Abstract: Introduction: The usefulness of positive expiratory pressure (PEP) through a PEP valve to enhance expiratory flow and improve cough efficiency is well known in children with tracheoesophageal fistula (TEF) and residual tracheomalacia. Gastroesophageal reflux (GER) is one of the most frequent complications encountered in patients with repaired esophageal atresia (EA) ± TEF. The impact of airway clearance techniques with a PEP valve on GER is not well defined in this group of patients. The aim of this prospective study was to determine the effects of PEP chest physiotherapy on GER burden measured by multichannel intraluminal impedance and pH monitoring (MII-pH) in EA/TEF children. Since the study is still ongoing, preliminary results are hereby presented. Methods: EA/TEF patients with tracheomalacia received three 20-min sessions of PEP chest therapy during the 24-hour MII-pH monitoring performed as a routine care. All children were off acid suppression therapy. The PEP session, performed after a 3-hour fasting period, consisted of 10 cycles lasting 1 minute of breathing with a PEP valve, followed by the forced expiratory technique and coughing. Esophageal acid exposure time (AET) and number of reflux episodes (RE) during each PEP session were measured as primary outcomes. Baseline impedance (BI) was also evaluated. MII-pH was defined abnormal if AET was >7% and/or the total RE was >70. Results: From January and December 2018, 5 consecutive male EA/TEF children (mean age 8.5 years; range 3–14 years) were enrolled. All of them showed low distal BI (1040 ± 143.2) and normal MII-pH findings (AET: 1.8 ± 2.9%; number of RE: 20.2 ± 9.0). Over the period of the PEP sessions, no significant changes in AET (0.0 ± 0.0), RE (0.6 ± 0.5), and BI were detected compared with the background monitoring. Conclusions: Although the limited number of participants prevents any definitive conclusions, our preliminary results indicate that PEP chest physiotherapy does not exacerbate GER in EA/TEF children. Continuation of the study across a larger sample of EA/TEF patients is needed to better define the effects of this simple chest physiotherapy technique on GER burden.